Respiratory pathology in the TDP-43 transgenic mouse model of amyotrophic lateral sclerosis - Biswas, Debolina D.; Sethi, Ronit; Woldeyohannes, Yochebed; Scarrow, Evelyn R.; El Haddad, Léa; Lee, Jane; ElMallah, Mai K. (Frontiers in Physiology, 2024)
Amyotrophic lateral sclerosis (ALS) is a devastating neurodegenerative disease that results in death within 2-5 years of diagnosis. Respiratory failure is the most common cause of death in ALS. Mutations in the transactive response DNA binding protein 43 encoded by the TARDBP gene are associated with abnormal cellular aggregates in neurons of patients with both familial and sporadic ALS. The role of these abnormal aggregates on breathing is unclear. Since respiratory failure is a major cause of death in ALS, we sought to determine the role of TDP-43 mutations on the respiratory motor unit in the Prp-hTDP-43 A315T mouse model -a model that expresses human TDP-43 containing the A315T mutation. We assessed breathing using whole-body plethysmography, and investigated neuropathology in hypoglossal and phrenic respiratory motor units. Postmortem studies included quantification of hypoglossal and putative phrenic motor neurons, activated microglia and astrocytes in respiratory control centers, and assessment of hypoglossal and phrenic nerves of TDP43 A315T mice. The male TDP43 A315T mice display an early onset of rapid progression of disease, and premature death (less than 15 weeks) compared to control mice and compared to female TDP43 A315T mice who die between 20-35 weeks of age. The TDP43 A315T mice have progressive and profound breathing deficits at baseline and during a respiratory challenge. Histologically, hypoglossal and putative phrenic motor neurons of TDP43 A315T mice are decreased and have increased microglial and astrocyte activation, indicating pronounced neurodegeneration and neuroinflammation. Further, there is axonopathy and demyelination in the hypoglossal and phrenic nerve of TDP43 A315T mice. Thus, the TDP-43 A315T mice have significant respiratory pathology and neuropathology, which makes them a useful translatable model for the study of novel therapies on breathing in ALS.